Internal Combustion Engines and Powertrain Systems for Future Transport 2019 : proceedings of the International Conference on Internal Combustion Engines and Powertrain Systems for Future Transport, (ICEPSFT 2019), December 11-12, 2019, Birmingham, UK /: proceedings of the International Conference on Internal Combustion Engines and Powertrain Systems for Future Transport, (ICEPSFT 2019), December 11-12, 2019, Birmingham, UK. (2019) - Unknown
No abstract available